Message Framing and Climate Change Communication: A Meta-Analytical Review - Nan Li; Leona Yi-Fan Su (Journal of Applied Communications, 2018)
This meta-analytic study reviewed experimental studies that examined the effects of message framing on public engagement with climate change. We included 10 studies that used self-reported measures of climate-related attitudes and behaviors, with 26 comparison pairs. The results suggested that message framing generally has a positive effect on individuals’ engagement with climate change and its two sub-categories – behavioral intentions and support for climate policy. More specifically, we found message frames that emphasize the environmental, economic, and moral dimensions of climate change have a small-to-medium size impact on individuals’ engagement with climate change. In contrast, message frames around public health implications or geographical identity barely influence individuals’ engagement with this issue. We discussed the implications on strategic communications of climate change.
Keywords: climate change; framing; emphasis frame; meta-analysis